2012
DOI: 10.1002/jbmr.1785
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid effects on changes in bone mineral density and cortical structure in childhood nephrotic syndrome

Abstract: The impact of glucocorticoids (GC) on skeletal development has not been established. The objective of this study was to examine changes in volumetric BMD (vBMD) and cortical structure over one year in childhood nephrotic syndrome (NS) and to identify associations with concurrent GC exposure and growth. Fifty-six NS participants, ages 5–21 years, were enrolled a median of 4.3 (0.5, 8.1) years after diagnosis. Tibia peripheral quantitative CT (pQCT) scans were obtained at enrollment and 6 and 12 months later. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 39 publications
5
39
1
1
Order By: Relevance
“…This is important, since DXA does not differentiate between these two structures, yet studies have shown divergent effects of GC on the two compartments [41]. Tsampalieros et al [42] recently studied a longitudinal cohort of pediatric NS treated with a similar initial GC regime as in our study, and found that tibia trabecular volumetric BMD Z-scores were lower and cortical density and area Z-scores higher compared to controls around the time of diagnosis. Over the one-year follow-up period, trabecular and cortical BMD Z-scores did not change significantly; however, there was a decrease in cortical area Z-score that was hypothesized to result from a dampening effect of GC therapy on cortical modeling (i.e.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This is important, since DXA does not differentiate between these two structures, yet studies have shown divergent effects of GC on the two compartments [41]. Tsampalieros et al [42] recently studied a longitudinal cohort of pediatric NS treated with a similar initial GC regime as in our study, and found that tibia trabecular volumetric BMD Z-scores were lower and cortical density and area Z-scores higher compared to controls around the time of diagnosis. Over the one-year follow-up period, trabecular and cortical BMD Z-scores did not change significantly; however, there was a decrease in cortical area Z-score that was hypothesized to result from a dampening effect of GC therapy on cortical modeling (i.e.…”
Section: Discussionmentioning
confidence: 51%
“…Given the high cortical density and low trabecular Z-scores observed at diagnosis and after 12 months of GC therapy in the study by Tsampelieros et al [42], when these two compartments are combined in the anterior-posterior DXA measurement, any net changes in the sum of the compartments must be considered in view of the more limited DXA technique. As such, longitudinal observations that show increases in BMD Z-scores by DXA over time (such as in our report) need to consider that such increases could arise from an increase in cortical density (which may not be beneficial to bone strength), or improvement in previously low trabecular density.…”
Section: Discussionmentioning
confidence: 99%
“…If AN induces suppression of cortical modeling, older bone with greater material density will accumulate, leading to greater cortical vBMD. This effect has been previously described in cohorts of children and adolescents receiving chronic glucocorticoid therapy for renal disease [17, 32]. Long-term glucocorticoid therapy led to reduced bone formation markers, decreased height Z-scores, and elevated cortical vBMD Z-scores [32].…”
Section: Discussionmentioning
confidence: 58%
“…This effect has been previously described in cohorts of children and adolescents receiving chronic glucocorticoid therapy for renal disease [17, 32]. Long-term glucocorticoid therapy led to reduced bone formation markers, decreased height Z-scores, and elevated cortical vBMD Z-scores [32]. This finding is of concern, since too much bone mineralization can lead to brittle bones [33] and thus to increased fracture risk [34, 35].…”
Section: Discussionmentioning
confidence: 66%
“…Significant decrease in bone mineral density has been found in chronic users of glucocorticoids [186][187][188][189]. Even high levels of natural glucocorticoids in the body are also associated with reduced bone-forming and increased bone breakdown [190].…”
Section: Glucocorticoidsmentioning
confidence: 99%